Genomic organization and reproductive regulation of a large lipid transfer protein in the varroa mite, Varroa destructor (Anderson & Trueman). Issue 5 (3rd July 2013) - Cabrera, A. R.; Shirk, P. D.; Duehl, A. J.; Donohue, K. V.; Grozinger, C. M.; Evans, J. D.; Teal, P. E. A.
Abstract: The complete genomic region and corresponding transcript of the most abundant protein in phoretic varroa mites, V arroa destructor (Anderson & Trueman), were sequenced and have homology with acarine hemelipoglycoproteins and the large lipid transfer protein (LLTP) super family. The genomic sequence of Vd LLTP included 14 introns and the mature transcript coded for a predicted polypeptide of 1575 amino acid residues. Vd LLTP shared a minimum of 25% sequence identity with acarine LLTPs. Phylogenetic assessment showed Vd LLTP was most closely related to M etaseiulus occidentalis vitellogenin and LLTP proteins of ticks; however, no heme binding by Vd LLTP was detected. Analysis of lipids associated with Vd LLTP showed that it was a carrier for free and esterified C12 ‐C22 fatty acids from triglycerides, diacylglycerides and monoacylglycerides. Additionally, cholesterol and β‐sitosterol were found as cholesterol esters linked to common fatty acids. Transcript levels of Vd LLTP were 42 and 310 times higher in phoretic female mites when compared with males and quiescent deutonymphs, respectively. Coincident with initiation of the reproductive phase, Vd LLTP transcript levels declined to a third of those in phoretic female mites. Vd LLTP functions as an important lipid transporter and should provide a significant RNA interference target for assessing the control of varroa mites.